Charting Literary Urban Studies Texts as Models of and for the City - Gurr, Jens Martin (Taylor & Francis, 2021)
Guided by the multifaceted relations between city and text, Charting Literary Urban Studies: Texts as Models of and for the City attempts to chart the burgeoning field of literary urban studies by outlining how texts in varying degrees function as both representations of the city and as blueprints for its future development. The study addresses questions such as these: How do literary texts represent urban complexities - and how can they capture the uniqueness of a given city? How do literary texts simulate layers of urban memory - and how can they reinforce or help dissolve path dependencies in urban development? What role can literary studies play in interdisciplinary urban research? Are the blueprints or 'recipes' for urban development that most quickly travel around the globe - such as the 'creative city', the 'green city' or the 'smart city' - really always the ones that best solve a given problem? Or is the global spread of such travelling urban models not least a matter of their narrative packaging? In answering these key questions, this book also advances a literary studies contribution to the general theory of models, tracing a heuristic trajectory from the analysis of literary texts as representations of urban developments to an analysis of literary strategies in planning documents and other pragmatic, non-literary texts.